TRAF3 and NBR1 both influence the effect of the disease‐causing CYLD(Arg936X) mutation on NF‐κB activity. Issue 11 (17th May 2021) - Danis, Judit; Kelemen, Evelyn; Rajan, Neil; Nagy, Nikoletta; Széll, Márta; Ádám, Éva
Abstract: Recently described Hungarian and Anglo‐Saxon pedigrees that are affected by CYLD cutaneous syndrome (syn: Brooke‐Spiegler syndrome (BSS)) carry the same disease‐causing mutation (c.2806C>T, p.Arg936X) of the cylindromatosis (CYLD) gene but exhibit striking phenotypic differences. Using whole exome sequencing, missense genetic variants of the TRAF3 and NBR1 genes were identified in the affected family members of the Hungarian pedigree that are not present in the Anglo‐Saxon pedigree. This suggested that the affected proteins (TRAF3 and NBR1) are putative phenotype‐modifying factors. An in vitro experimental system was set up to clarify how wild type and mutant TRAF3 and NBR1 modify the effect of CYLD on the NF‐κB signal transduction pathway. Our study revealed that the combined expression of mutant CYLD(Arg936X) with TRAF3 and NBR1 caused increased NF‐κB activity, regardless of the presence or absence of mutations in TRAF3 and NBR1. We concluded that increased expression levels of these proteins further strengthen the effect of the CYLD(Arg936X) mutation on NF‐κB activity in HEK293 cells and may explain the phenotype‐modifying effect of these genes in CYLD cutaneous syndrome. These results raise the potential that detecting the levels of TRAF3 and NBR1 might help explaining phenotypic differences and prognosis of CCS.